Purple Jacaranda - Mayer, Claude-Hélène,Wolting, Stephan (Waxmann, 2016)
Stories and autobiographical narrations have particular importance in society, whether they are told, shared or just listened to. This book presents 19 narrations of authors about their own experiences as migrants. Coming from different parts of the world, they tell stories about struggles, development, doubt, challenges, hope and empowerment, sometimes amusing the reader and then again containing a saddening or thought-provoking undertone. These creative works are set in various cultural contexts such as for example Germany, Australia, South Africa, America, India or Hungary and describe how life experiences in different countries contribute to and influence the development of transcultural identities. This book is a must for readers interested in transcultural stories, creative writing and identity development in cultural and transcultural contexts. Together with 18 contributing authors Mayer and Wolting have compiled 19 quite diverse individual transcultural accounts, perceptions and identity developments. That gives us a pool of first hand shared experiences with a glimpse into the joys, challenges and emotions that transcultural individuals encounter and have to cope with. The unique ways and solutions can encourage us, serve as role models or lead to deeper insight. – Tatjana van de Kamp on: socialnet.de
Keywords: interkulturelle Kommunikation; Interkulturelle Kommunikation; Persönlichkeitsentwicklung; Identität; Biography; Personality Development; Biographie; Identity; Germanistik; Biographie und Lebenslauf; Intercultural Communication; transkulturell; Austausch; Transcultural; exhange; Biographieforschung